Existence and multiplicity results for fractional p(x)-Laplacian Dirichlet problem - Chakrone O.; Belhadj K.; Sidi Ammi M. R.; Zerouali A. (Moroccan Journal of Pure and Applied Analysis, 2022)
In this paper, we study a class of fractional p(x)-Laplacian Dirichlet problems in a bounded domain with Lipschitz boundary. Using variational methods, we prove in different situations the existence and multiplicity of solutions.